The role of circulating platelet transcripts. (June 2015) - Clancy, L.; Freedman, J. E.
Summary: Our understanding of platelets, anucleate cells with a traditional role in hemostasis and inflammation, has developed greatly over the last decade. Platelets' role in the systemic response of the body to vascular injury, inflammation, and infection has expanded as has our understanding of their importance to the body's regulation of these processes. One recently explored mechanism by which platelets regulate the body's inflammatory and immune response is through its endogenous RNA. Platelets' messenger RNA (mRNAs) and microRNA (miRNAs) profiles have been shown to reflect disease and disease risk factors and have been correlated with select human clinical phenotypes. Developing an understanding of platelet transcripts in the circulation elucidates how platelets function in both their traditional thrombotic role and non‐traditional functions and may have widespread implications in several fields including thrombosis, infection, cancer, and systemic inflammation.